Implementation of ICT-Based Management Information Systems in Increasing the Effectiveness of Students’ Learning at State Vocational School 1 Gelumbang - Aini, Fitri; Fitria, Happy; Wahidy, Achmad (Journal of Social Work and Science Education, 2024)
This study aims to describe and analyze the implementation of an ICT-based management information system as well as the supporting and inhibiting factors in increasing the effectiveness of student learning. This research is qualitative and was conducted at SMK Negeri 1 Gelumbang, Muara Enim Regency, south Sumatera Province. techniques for collecting data from observations, interviews, and documentation. The results of this research show that the application of management information systems at SMK Negeri 1 Gelumbang in learning activities is generally ICT-based. The application of a manual or physical-based management information system is only carried out to overcome the obstacles that occur in the delivery of information on learning activities. The application of an ICT-based sim can be seen in all computerized data, management, and delivery of information on learning activities by using Google Classroom, WhatsApp groups, Telegram, PowerPoint, learning videos (YouTube), Quizizz, Wordwall, Web-Learning, and blogs so as to increase effectiveness in learning. To overcome the obstacles of ICT-based learning that cannot be overcome, the delivery of information is done manually or physically in the form of hard copies of materials, learning assignments, evaluations, and library books.